Characterization of Oral Immunity in Cases and Close Household Contacts Exposed to Andes Orthohantavirus (ANDV) - Martinez-Valdebenito, Constanza; Andaur, Camila; Angulo, Jenniffer; Henriquez, Carolina; Ferrés, Marcela; Le Corre, Nicole (Frontiers in Cellular and Infection Microbiology, 2020)
Background: Andes orthohantavirus (ANDV) is the sole etiologic agent of Hantavirus Cardiopulmonary Syndrome in Chile and, until now, the only Hantavirus known to be transmitted by person-to-person route. The main risk of person-to-person transmission is to be a sexual partner of an index case, and deep kissing the main mechanism of infection. Experimental reports suggest that ANDV infection can be inhibited by determined saliva components. Therefore, some host factors like saliva components, could explain why some individuals became infected even though their exposure to the virus is high. Aim: To compare some saliva components, such cytokines and mucins, between ANDV-infected cases (exposed-sick), their close household contacts (exposed-not sick) and healthy control not exposed. Methods: 69 confirmed ANDV-infected cases, 76 close household contacts exposed to ANDV but not infected (CHC) and 39 healthy control not exposed (HCNE). The following components were measured in saliva: secretory immunoglobulin A (sIgA) by ELISA; cytokines (IL1β, IL12p70, TNFα, INFy, IL10, IL6, VEGF, IP10 and IL8) by Multiplex Assay and mucins MUC7 and MUC5B by Western Blotting. Results: Among infected cases, CHC and HCNE analyzed 74%, 45% and 33% were men, respectively (p ≤ 0.05). The average age for cases, CHC and HCNE was 37.7, 28.7 and 32 years, respectively (p ≤ 0.05). The average concentration of sIgA in infected cases was 4.846 mg/mL and for CHC group 0.333 mg/mL (p ≤ 0.05). For cytokines, significant differences were found comparing all groups for IFNy, IL12p70 and IL8. Among CHC group, there was a higher frequency of detection of MUC7 isoform (62.6%; 31/49) compared to ANDV-infected cases (40.5%; 17/42) (p <0.05). Similarly, presence of MUC5B was higher among CHC groups (62.16%; 46/74) than in ANDV-infected cases (44.4%; 28/63) (p <0.05). Conclusions: Three salivary components show differences between infected cases and close household contacts (sIgA, cytokines and mucins). These differences can be explained by the acute state of the disease in the ANDV-infected cases group. However, the differences in MUC5B and isoforms of MUC7 are not entirely explainable by the infection itself. This work represents a novel description of salivary components in the context of ANDV infection.